Soil suitability evaluation for crop selection using fuzzy sets methodology - Amin SHARIFIFAR; Hadi GHORBANI; Fereydoon SARMADIAN (Acta Agriculturae Slovenica)
In this study appraisal of four different agricultural land evaluation methods including the so-called Storie method, square root method, maximum limitation method and fuzzy sets method, was done. The study was performed in Bastam region, located in Semnan province at the north east of Iran. Three crops including tomato, wheat and potato were assessed for the purpose of this research. Soil characteristics assessed were rooting depth, CaCo3, organic carboncontent, clay content, pH and slope gradient. Statistical analyses were done at significance levels of α = 0.1 and α = 0.05. Results of regression between land indices, calculated through the four methods, with observed yields of the crops, showed that the regression were significant in fuzzy sets method for all of the assessed crops at p = 0.05 but not significant in maximum limitation method for any of the crops. The Storie and square root methods also showed a significant correlation with wheat yield at p = 0.1. This study was a demonstrative test of fuzzy sets theory in land suitability evaluation for agricultural uses, which revealed that this methodology is the most correct method in given circumstances.